The prognostic role of neopterin in COVID‐19 patients. Issue 3 (29th September 2020) - Ozger, Hasan Selcuk; Dizbay, Murat; Corbacioglu, Seref Kerem; Aysert, Pinar; Demirbas, Zehra; Tunccan, Ozlem Guzel; Hizel, Kenan; Bozdayi, Gulendam; Caglar, Kayhan
Abstract: In Coronavirus disease‐2019 (COVID‐19) cases, hyper inflammation is associated with the severity of the disease. High levels of circulating cytokines were reported in severe COVID‐19 patients. Neopterin produced by macrophages on stimulation with interferon‐gamma, which is an important cytokine in the antiviral immune response, hence it can be used to predict the severity of disease in COVID‐19 cases. In this study, it was aimed to determine the prognostic value of the neopterin for the prediction of severe disease in patients with COVID‐19. This single‐center, prospective study was conducted in hospitalized COVID‐19 patients and healthy volunteers. Severe and mild COVID‐19 cases were compared in terms of clinical and laboratory findings as well as serum neopterin levels on hospital admission. To assess the prognostic utility of neopterin between the severe and mild COVID‐19 groups, a receiver‐operating characteristic (ROC) curve was generated, and the area under the curve (AUC) was calculated. The median serum neopterin level was four times higher in COVID‐19 patients than the healthy controls (46 vs. 12 nmol/L; p < .001). The AUC value of serum neopterin was 0.914 (95% confidence interval, 0.85–0.97). The sensitivity and specificity of serum neopterin for the cut‐off value of 90 nmol/L to identify severe COVID‐19 cases were 100% and 76%, respectively. Serum neopterin levels on hospitalization were significantly higher in severe COVID‐19 disease than mild COVID‐19 patients. Neopterin levels can be used as an early prognostic biomarker for COVID‐19 on admission.